Narratives of Crisis and Independent Cinema: Production, Aesthetics, and Ideology in the Films of Ramin Bahrani - (:unkn) unknown (My University, 2021)
This dissertation examines the first six U.S. feature films of Iranian-American director Ramin Bahrani in order to explore key connections between various industrially independent production modes and the aesthetic and ideological qualities of the films. Bahrani’s films are divided into three distinct periods based on the production mode in which he was working at the time, here characterized as microbudget, guerilla-style independent, Indiewood, and digital streaming productions. Each chapter explores the production mode in question, including production histories of the relevant films, and then discusses key connections arising between production strategies, aesthetics, and the films’ ideological and historical import. Ultimately this dissertation raises questions about how what “independence” means in a contemporary and increasingly digital filmmaking landscape, as well as how audiences are asked to receive and understand socio-politically engaged films via aesthetics, production narratives, and exhibition context.
Keywords: Cinematic Realisms; Film aesthetics; Film production; Ramin Bahrani; U.S. Independent Cinema